1956
DOI: 10.1002/ajpa.1330140219
|View full text |Cite
|
Sign up to set email alerts
|

Physical growth of the rhesus monkey (Macaca mulatta)

Abstract: 9215 9285 9370 9525 9585 9665 9745 9815 9890 9970 S.D. 920 695 695 690 685 700 720 745 770 795 820 855 NO. 6 S.D. 825 850 880 905 935 965 985

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
47
0

Year Published

1969
1969
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(56 citation statements)
references
References 14 publications
9
47
0
Order By: Relevance
“…Yale rhesuses at the age of ca. 7.0 years (Indian-origin: van Wagenen and Catchpole, 1956) had a CRL comparable with the PRI Indian-derived rhesuses, but the latter had relatively shorter thighs and longer legs. Cayo Santiago rhesuses (Indian-origin: Turnquist and Kessler, 1989), which were reared under semi-wild conditions, were slightly larger than the PRI rhesuses not only in CRL but also in limb segment lengths by up to 13%.…”
Section: Principal Component Analysismentioning
confidence: 89%
See 1 more Smart Citation
“…Yale rhesuses at the age of ca. 7.0 years (Indian-origin: van Wagenen and Catchpole, 1956) had a CRL comparable with the PRI Indian-derived rhesuses, but the latter had relatively shorter thighs and longer legs. Cayo Santiago rhesuses (Indian-origin: Turnquist and Kessler, 1989), which were reared under semi-wild conditions, were slightly larger than the PRI rhesuses not only in CRL but also in limb segment lengths by up to 13%.…”
Section: Principal Component Analysismentioning
confidence: 89%
“…Although some morphological evaluations have been conducted on rhesuses from various localities (Fooden, 1964(Fooden, , 1971(Fooden, , 1997(Fooden, , 2000Jiang et al, 1991) and colonies (van Wagenen and Catchpole, 1956;Gavan and Hutchinson, 1973;DeRousseau and Reichs, 1987;Turnquist and Kessler, 1989;Clarke and O'Neil, 1999), detailed morphometric comparisons have not been made. In particular, only few studies have reported on the body size and proportions of macaques based on standardized morphometric methods (Iwamoto, 1971;Hamada et al, 1986Hamada et al, , 1996.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we chose the rhesus fetus as our experimental model because subhuman primates are biologically more similar to humans than are the lower animals. VAN WAGENEN and CATCHPOLE [25] have investigated the physical growth of the rhesus monkey and concluded that the pattern of growth parallels in a foreshortened, but remarkably similar form, that of man. The differentiation of muscle fibers for the rhesus and man has been shown histochemically to be similar [l, 121.…”
Section: Introductionmentioning
confidence: 99%
“…Although the growth of many species of Macaca has been studied by many au thors,detailed studies have not been published except in the case of M. mulatta (van Wagenen and Catchpole, 1956;Watts and Gavan, 1982;Tanner et al, 1990). Moreover, such studies tend to be limited to a particular growth period and/or to certain bodily sizes.…”
mentioning
confidence: 99%